Effectivity Of Single Identity Number (SIN) In Implementation Of KTP Electronic - Nurani, Juli; Rimbawani S., Vera; Abdul Razak, Darwin; Ratnawati, Susi (Advances in Social Sciences Research Journal, 2018)
One of the problems that are now emerging and intractable associated with the development of information systems in various institutions / agencies in Indonesia is the heterogeneity of the network , hardware , OS , programming language , developers , database , and the number of unique identity number used . Project -based e-ktp card valid SIN who are expected to be nationally significant improvement steps. Development of information system of e-ktp card equipped with occupancy database that stores the database associated with the identity of every citizen over the age of 17 years and / or married. Various attempts have been made , among others, introduced the concept of a Single Identity Number ( SIN ) . SIN is a unique number that is integrated in the identity card of a citizen . SIN and identity cards will form a national population database that can be the only reference to a variety of public service applications . ( http://news.viva.co.id/ ) This study wants to assess the effectiveness of the application of komprehansif about single identity number ( SIN ) in the implementation of e -ktp card to realize good governance The target of this study is to examine the effectiveness of the application of single identity number ( SI ) , and examines how the implementation of e-ktp model using kosep single identity number is implemented . In this study the authors used a qualitative approach . As for the data collection was done with a quick survey , indept interview and observation . Results: policy and regulatory support required to realize the national population database as a prerequisite for good governance . In the future , the presence of SIN and national identity cards population , will facilitate the implementation of biometric data . Biometric data guarantee uniqueness of one’s identity card ownership .